Naphthalene crystal shape prediction from molecular dynamics simulations. Issue 21 (9th May 2019) - Bjelobrk, Zoran; Piaggi, Pablo M.; Weber, Thilo; Karmakar, Tarak; Mazzotti, Marco; Parrinello, Michele
Abstract : The crystal shape of naphthalene grown from ethanol solution at constant supersaturation was predicted using state-of-the-art molecular dynamics simulations. Abstract : We used molecular dynamics simulations to predict the steady state crystal shape of naphthalene grown from ethanol solution. The simulations were performed at constant supersaturation by utilizing a recently proposed algorithm [Perego et al., J. Chem. Phys., 2015, 142, 144113]. To bring the crystal growth within the timescale of a molecular dynamics simulation we applied well-tempered metadynamics with a spatially constrained collective variable, which focuses the sampling on the growing layer. We estimated that the resulting steady state crystal shape corresponds to a rhombic prism, which is in line with experiments. Further, we observed that at the investigated supersaturations, the {001̄} face grows in a two step two dimensional nucleation mechanism while the considerably faster growing faces {11̄0} and {201̄} grow new layers with a one step two dimensional nucleation mechanism.